Fast and High‐Throughput Synthesis of Medium‐ and High‐Entropy Alloys Using Radio Frequency Inductively Coupled Plasma. Issue 3 (30th November 2020) - Zhu, Bo; Alavi, Sina; Cheng, Changjun; Sun, Haokun; Zhao, Hongwei; Kim, Keun Su; Mostaghimi, Javad; Zou, Yu
Abstract : Multiprincipal element alloys, or medium‐ and high‐entropy alloys (MEAs and HEAs), hold great potential for numerous structural and functional applications, yet the synthesis of such alloys out of a vast composition space is a daunting task. Herein, a radio frequency inductively coupled plasma (RF‐ICP) method for preparing bulk MEAs and HEAs in a rapid and high‐throughput fashion is reported. Typical MEAs and HEAs are successfully synthesized within 40 s per alloy, thereby greatly improving the fabrication efficiency and throughput. This method provides a new opportunity to accelerate the discovery of new complex alloys for a broad range of applications. Abstract : Discovery of medium‐ and high‐entropy alloys out of a vast composition space is a daunting task. A radio frequency inductively coupled plasma method for preparing such alloys in a rapid (<40 s per alloy) and high‐throughput fashion is reported, thereby greatly improving the efficiency in navigating their design space.